Propofol Use for Sedation during Endoscopy in Adults: A Canadian Association of Gastroenterology Position Statement. (2008) - Byrne, Michael F; Chiba, Naoki; Singh, Harminder; Sadowski, Daniel C; for the Clinical Affairs Committee of the Canadian Association of Gastroenterology,
Abstract : Over the past decade, multiple clinical reports have demonstrated that the use of propofol sedation for gastrointestinal endoscopy by gastroenterologists and trained endoscopy nurses is safe and effective in appropriately selected patients. Proposed benefits of propofol sedation include rapid onset of action, improved patient comfort and rapid clearance, as well as prompt recovery and discharge from the endoscopy unit. As a result of medical evidence, a number of international professional societies have endorsed the use of propofol in gastrointestinal endoscopy. In Canada, no formal guidelines currently exist. In the present article, the Clinical Affairs Committee of the Canadian Association of Gastroenterology presents a position statement, incorporating updated information on the use of propofol sedation for endoscopy in adult patients.